Participatory Integrated Climate Services for Agriculture (PICSA) Specialist Intermediary Training in Nyamata, Rwanda - Nsengiyumva, Gloriose; Kagabo, Desire M.; Clarkson, Graham; Dorward, Peter (2017)
The Rwanda Climate Services for Agriculture project is a four-year initiative (2016-2019) that seeks to transform Rwanda’s rural farming communities and national economy through improved climate risk management. This report presents the outputs of a five-day training on the use of a Participatory Integrated Climate Services for Agriculture (PICSA) approach to help farmers make climate informed decisions. This training brought together key government agencies in Rwanda, research organizations, farmers’ representatives, development partners, non-governmental organizations, and media. The one week training workshop aimed to initiate the process to develop skills of staff to become a group of expert trainers in the PICSA approach. The report includes the proceeding of the training workshop as well as reflections on workshop outcomes and feedback by participants.